Pengaruh derajat keasaman pH saliva terhadap angka kejadian karies gigi (DMF-T) anak sekolah dasar umur 9-14 tahun 2018 - Rusmali, Rusmali; Abral, Abral; Ibraar Ayatullah, Muhammad (Poltekkes Kemenkes Yogyakarta, 2019)
The incidence of dental caries in children is very vulnerable because children have not been able to maintain dental and oral hygiene, one effort that can be done is to provide education in the form of how to brush teeth properly and correctly. The next step is to help the teeth to be more resistant to acid due to the acidogenic metabolism of plaque and food scraps, one of which can be done is smearing the teeth with a fluoride solution. This fluorine solution works or binds the arrangement of interpreting to become denser so that the acid from the results of metabolism by germs so that there is no demineralization of tooth enamel. This study aims to describe the effect of the application of SnF or NaF fluorine to Saliva pH of 9-14-year-old elementary school children in Pontianak City in 2018. The research method uses Explanatory Research, surveys with direct examination to apply SnF or NaF fluorine and salivary pH measurements with a paper indicator to see the pH of saliva. The type of research used is descriptive analytics, to see the average Saliva pH after fluorine application, see the effect of fluorine application, see the magnitude of the influence of R2 and see the level of verification. The test used in Regression. The results of the research conducted on 186 samples obtained the average data, namely female respondents as much as 52.2%, age of 11 years old elementary school children as much as 33.3%, Saliva 7 pH as much as 58.6%, fluorine application (R) effect amounted to .45, the amount of influence (R2) of fluorine application is 45% and Siq value. 0,000 <0,005. The conclusion is that the effect of the application of SnF or NaF fluorine to Saliva pH in elementary school age children aged 9-14 years with an average pH 7 (58.6%) with a magnitude of fluorine influence of 45%, the level of qualification is very strong because of the value siq. 0,000 <0,005.